2019
DOI: 10.3390/cells8101114
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil-to-Lymphocyte Ratio is Related to Disease Activity in Relapsing Remitting Multiple Sclerosis

Abstract: Background: The role of the neutrophil-to-lymphocyte ratio (NLR) of peripheral blood has been investigated in relation to several autoimmune diseases. Limited studies have addressed the significance of the NLR in terms of being a marker of disease activity in multiple sclerosis (MS). Methods: This is a retrospective study in relapsing–remitting MS patients (RRMS) admitted to the tertiary MS center of Catania, Italy during the period of 1 January to 31 December 2018. The aim of the present study was to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 21 publications
5
38
0
3
Order By: Relevance
“…However, we investigated the associations in the subset according to adjuvant chemotherapy. Furthermore, it should be recognized that NLR is a nonspecific parameter, and it could be influenced by concomitant diseases, such as infection, autoimmune disease, or stroke 11 , 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…However, we investigated the associations in the subset according to adjuvant chemotherapy. Furthermore, it should be recognized that NLR is a nonspecific parameter, and it could be influenced by concomitant diseases, such as infection, autoimmune disease, or stroke 11 , 46 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…While T cells are recognized as the main driver of MS, elevated numbers of other peripheral leukocytes have been observed in the CNS, suggesting they may also have effector functions in MS. Specifically, a recent report demonstrated that MS patients have a higher circulating neutrophil-to-lymphocyte ratio compared to healthy controls, and the ratio increases with relapse and aggravated disability [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…According to modern notions, MS is a multifactorial chronic progressive disease characterized by central nervous system damage. The process of demyelination based on mechanisms that mutually reinforce each other: inflammatory response, neurodegeneration with abnormal remyelination and axonal damage (primary or secondary) [1]. There are many publications on studies of the ratio of neutrophils to lymphocytes as a marker of inflammation in MS [1,2,5].…”
Section: Discussionmentioning
confidence: 99%